The test taker's fallacy: How students guess answers on multiple‐choice tests. (5th September 2018) - Lee, Chan Jean
Abstract: Many students and applicants take multiple‐choice tests to demonstrate their competence and achievement. When they are unsure, they guess the most likely answer to maximize their score. Despite the impact of guessing on test reliability and individual performance, studies have not examined how patterns of answer sequences in multiple‐choice tests affect guessing. This research presents the test taker's fallacy, which refers to an individual's tendency to expect a different answer to appear for the next question given a run of the same answer choices. The test taker's fallacy exhibits negative recency, similar to the gambler's fallacy. However, extending the sequential judgment literature, the test taker's fallacy shows that negative recency arises even when sequences may or may not be randomly generated. In three studies, including a survey and experiments, the test taker's fallacy is robustly observed. The test taker's fallacy is consistent with the operation of the representativeness heuristic. This research explains what and how test takers guess given a streak of answers and extends judgment under uncertainty to the test‐taking context.